Revitalizing Loyalty: Unveiling the Dynamics of E-Service Quality, Customer Satisfaction, and Trust in Amplifying User Engagement with Electricity Mobile Application - Rahayu Hafiza; Yeshika Alversia (Publikasi Indonesia, 2024)
The development of internet-based technology and the increasing use of smartphones have become essential tools for companies to enhance their online service quality. This research aims to analyze the influence of e-service quality, customer satisfaction, and customer trust on loyalty intention in optimizing the utilization of the PLN Mobile application. This study employs a quantitative approach using an online questionnaire to collect data from 386 respondents using the PLN Mobile application. The data are then analyzed using structural equation modeling. The results of this study reveal that e-service quality has a significant positive impact on customer satisfaction and customer trust. Furthermore, customer satisfaction and customer trust are found to have a positive and significant influence on repurchase intention and word of mouth in optimizing application usage. These findings have significant implications in the energy and information technology industries, particularly in developing strategies to enhance the utilization of electricity mobile applications.